2019
DOI: 10.1177/1077559519866272
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Community- and Home-Based Interventions to Support Parenting and Reduce Risk of Child Maltreatment Among Families With Substance-Exposed Newborns

Abstract: Substance-exposed newborns (SENs) are at increased risk of child maltreatment, out-of-home placement, and poor health and developmental outcomes. The purpose of this systematic review is to synthesize existing research on community- and home-based interventions designed to improve parenting and reduce risk of maltreatment for families with SENs, applying a program logic framework. The review includes studies that used preexperimental, quasi-experimental, and experimental designs. Twelve interventions were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
(88 reference statements)
0
11
0
Order By: Relevance
“… Empower Communities . Communities are the mechanism that can care for children and families long-term ( West et al, 2020 ). As NGOs are limited in what services they can provide, strengthening community resources and networks to enhance response to the pandemic and associated restrictions encourages a framework that can safeguard children and support families now and in the future.…”
Section: Discussionmentioning
confidence: 99%
“… Empower Communities . Communities are the mechanism that can care for children and families long-term ( West et al, 2020 ). As NGOs are limited in what services they can provide, strengthening community resources and networks to enhance response to the pandemic and associated restrictions encourages a framework that can safeguard children and support families now and in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to acknowledge that this was not a predetermined criterion, instead, this was the evidence remaining after a detailed screening process. In line with published systematic reviews within this field (Coulton et al., 2007; van Dijken, Stams, & de Winter, 2016; West et al., 2019), the database search was limited to four databases in addition to specific journal search. It is important to acknowledge that though an exhaustive search was performed, it is possible to miss out on a few articles in other databases.…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, while substance use treatment is certainly paramount for improving health and safety for mothers and babies with PSE, prior research has shown that substance use treatment alone for these families is insufficient in reducing the risk of child maltreatment. To ensure safety, other family needs must be addressed, such as specialized parenting support integrated into substance use services (Marsh, Smith, & Bruni, 2011; West et al, 2020). Moreover, while pregnancy is a temporary period of a birthing woman's life, neuroscience research has demonstrated that addiction is a chronic medical condition characterized by relapse; therefore, comprehensive services should ideally occur throughout the life course, in addition to preconception, pregnancy, and postpartum periods among families affected by SUD (Faherty, Stein, & Terplan, 2020; Marsh et al, 2011).…”
Section: The Opioid Epidemic and Child Maltreatmentmentioning
confidence: 99%
“…Finally, reflected in CAPTA's interdisciplinary, public health approach to family care planning, research suggests that one‐size‐fits‐all approaches are ineffective in addressing the unique and multiple risk factors often associated with newborns affected by PSE, such as excessive crying or maternal isolation (West et al, 2020). A growing body of literature points to the importance of utilizing evidence‐based interventions that are both developmentally and trauma informed, including the use of attachment‐based approaches addressing caregiving skills (Suchman, 2016; West et al, 2020).…”
Section: Capta: Mandates and Goalsmentioning
confidence: 99%